A video-game group intervention: Experiences and perceptions of adults with chronic stroke and their therapists: Intervention de groupe à l'aide de jeux vidéo : Expériences et perceptions d'adultes en phase chronique d'un accident vasculaire cérébral et de leurs ergothérapeutes. (April 2018) - Rand, Debbie; Givon, Noa; Avrech Bar, Michal
Background: Ongoing physical activity is important for maintaining the functional level of individuals with chronic stroke. Video games in a group setting might be a cost-effective way for providing mobility and preventing physical inactivity. Purpose: This study explores the experiences and perceptions of individuals with chronic stroke who participated in a novel community-based video-game group intervention and their therapists. Method: A qualitative study, nested in a randomized controlled trial, was conducted using semistructured interviews with eight individuals with chronic stroke (four men and four women) ages 29 to 69 and a focus group of their three occupational therapists, following a video-game intervention. Data were analyzed using content analysis. Findings: Three main categories were identified by the study participants: (a) using video games, (b) the group/team experience, and (c) intervention outcomes/evolving understandings following the intervention. Implications: Playing video games was perceived not as treatment but as a motivating tool to facilitate whole-body movement. Therefore, this intervention might be suitable to be used in the community for ongoing intervention.